The Role of Organizational Commitments in Mediating the Locus of Control on Auditor Performance - Sundari, Siti; Hastuti, Sri; Sari, Rida Perwita; Sari, Rika Puspita (Nusantara Science and Technology Proceedings, 2020)
This study aims to prove the role of organizational commitment as a mediator on the effect of locus of control on auditor performance. The research data were collected by questionnaire, with a sample of 88 auditors working in public accounting firms in the cities of Surabaya and Malang, East Java. Data analysis was done using Path Analysis with Smart PLS software. The research shows that locus of control has a positive effect on auditor performance, organizational commitment has a positive impact on auditor performance, and organizational commitment is a mediator of locus of control on auditor performance.